2007
DOI: 10.1111/j.1365-2869.2007.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the initial ventilatory response to hypoxia in sleeping infants

Abstract: SUMMAR Y In infants most previous studies of the hypoxic ventilatory response (HVR) have been conducted only during quiet sleep (QS) and arousal responses have not been considered. Our aim was to quantify the maturation of the HVR in term infants during both active sleep (AS) and QS over the first 6 months of life. Daytime polysomnography was performed on 15 healthy term infants at 2-5 weeks, 2-3 and 5-6 months after birth and infants were challenged with hypoxia (15% O 2 , balance N 2 ). Tests in AS always re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 30 publications
(64 reference statements)
7
26
4
1
Order By: Relevance
“…In addition to standard paediatric polysomnographic recording electrodes (Parslow et al. , 2003, 2004; Richardson et al. , 2007) nasal airflow was measured using a pneumotachograph attached to a silicone rubber nose‐mask (Parslow et al.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to standard paediatric polysomnographic recording electrodes (Parslow et al. , 2003, 2004; Richardson et al. , 2007) nasal airflow was measured using a pneumotachograph attached to a silicone rubber nose‐mask (Parslow et al.…”
Section: Methodsmentioning
confidence: 99%
“…Research in this area has focused on physiological responses to air challenges. In term infants, normal biphasic responses to hypoxia were present at 2–5 weeks, 2–3 months, and 5–6 months postnatal (Richardson et al, 2007; Verbeek et al, 2008). In preterm infants, the ventilatory response to hypoxia appears to transition from a monophasic depressive response at 31.5 weeks post-conception (Alvaro et al, 1992) to a biphasic response by 35.5 weeks post-conception (Martin et al, 1998) and is still present at 45 weeks post-conception (Verbeek et al, 2008).…”
Section: Prematurity and Sidsmentioning
confidence: 99%
“…Likewise, at 1–3 months of age control infants had lower drops in oxygen saturation when exposed to hypoxia/hypercapnia than infants of smoking mothers (Campbell et al, 2001). It is also interesting to note that during hypoxic challenges, preterm infants have greater drops in oxygen saturation early in life (2 weeks to 3 months) compared to later (5–6 months), while term infants tend to maintain oxygen saturation early (2–3 weeks) and become more sensitive at later ages (2–6 months) (Horne et al, 2002; Richardson et al, 2007; Verbeek et al, 2008). Differences such as these may help to account for the earlier occurrence of SIDS in preterm infants.…”
Section: Prematurity and Sidsmentioning
confidence: 99%
“…In 1992 the American Academy of Pediatrics (AAP) issued a recommendation that ''healthy term infants'' be placed on their backs which resulted in a significant reduction in the incidence of SIDS [6]. Although studies have shown that there is a progressive maturation of the ventilatory response to hypoxia in the first 6 months of life, the actual age at which it converts to the adult type remains controversial [7]. There is some evidence that obstructive sleep apnea and its associated hypoxia may play a significant role in SIDS [8].…”
Section: Introductionmentioning
confidence: 99%